Impact of Information Quality on Customer Perceived Value, Experience Quality, and Customer Satisfaction from Using GoFood Aplication - Tundung Subali Patma; Nilawati Fienaningsih; Karisma Sri Rahayu; I Gusti Lanang Suta Artatanaya (Faculty of Economics and Business, Universitas Gadjah Mada, 2021)
Introduction/Main Objectives: The existence of technological advances in online transportation provides benefits to the community, and especially for the culinary industry; consumers no longer have to go to restaurants to buy food; it can be ordered through the Gojek application. The Gojek application makes it easy for people to buy food online. Various items of information about the restaurant are provided by Gojek’s online transportation service application. Background Problems: The government's appeal regarding COVID-19 requires people to stay at home, to support social distancing. Many activities must now be carried out at home, including eating. Along with the technological developments, people do not need to worry about staying at home because everything can be done from the home, with the GoFood application's support. Novelty: This study aims to determine and prove the effect of information quality on experience quality and customer perceived value, as well as satisfaction, from using the GoFood application in Malang City. This research is an update of the information gathered previously during the pandemic, which can be used as a reference for determining marketing strategies. Research Methods: This type of research is explanatory research through a quantitative approach, by conducting a direct survey of the application’s users, by using an online questionnaire. The research sample consists of 380 respondents. The sampling technique of this study was purposive sampling with the criteria that the Gojek application’s users had made purchases the application at least one times, and were aged 18 years and over, so the perceptions given would be quite clear and independent. Finding/Results: The results show that information quality has a positive and significant effect on experience quality, customer perceived value and customer satisfaction; experience quality has a positive and significant effect on customer perceived value; and customer perceived value has a positive and significant effect on customer satisfaction. Conclusion: This study reveals that the quality of the experience has a positive but insignificant effect on customer satisfaction. The result is a new finding from this study because there are differences in the previous studies' relationships between the variables. This study contributes that the stay-at-home appeal could increase the use of online applications to carry out activities.